Red macroalgae kappaphycus alvarezii as feedstock for nutraceuticals, pharmaceuticals and fourth generation biofuel production - Oliveira, L. E.; Cedeno, R. F. [UNESP]; Chavez, E. G. [UNESP]; Gelli, V. C.; Masarin, F. [UNESP] (My University, 2019)
Biorefineries intends to utilize algal biomass and their by-products at industrial scale. The macroalgae Kappa-phycus alvarezii has high content of carrageenan, which is a polysaccharide hydrocolloid, serving as a raw material for the production of third generation biofuels, food and pharma-ceuticals. The aim of this study is to show that besides these products, there is the potential for the production of a fourth generation biofuel. Two strains, brown and red, were selected based on their high growth rates and productivity and were treated with 6% KOH for extraction carrageenan extraction. The results of the chemical composition of this residue show that there is considerable amount of fermentable sugar in the carrageenan extraction residue. The glucan conversion was 100% for both strains, and the concentrations of glucose from the brown and red strains were 13.7 and 11.5 g L−1, respectively. The results highlight the efficiency of generating a key bioproduct from carrageenan residue. This would save the carrageenan that can be used for as a food thickener as it has been used for centuries. Thus, the biorefinery of K. alvarezii can be exploited not only to produce carrageenan, but also to generate glucose for future use in biofuel production.
Keywords: Biorefinary; Fourth generation biofuel; Residue of carrageenan extraction